Estimasi Stok Karbon Di Atas Permukaan Menggunakan Citra Sentinel-1A di Hutan Mangrove Karang Sewu, Bali - Nikmah Fitria Nuraini; I Wayan Gede Astawa Karang; I Nyoman Giri Putra (Journal of Marine Research and Technology, 2022)
Karang Sewu mangrove is one of the forests in the tropics that can store a higher amount of carbon compared to other forest. The researh of carbon storage in the Karang Sewu mangrove forest is required to support government policies in mitigating blue carbon. Research about above ground and below ground carbons in the Karang Sewu mangroves has not provided spatial information, and one of the techniques that can be used is remote sensing with Synthetic Aperture Radar (SAR). This research used SAR Sentinel-1A C-Band sensor imagery to estimate above-ground carbon in mangroves because it can penetrate the canopy to branch vegetation so that the backscatter value is not disturbed by water on the surface. The purpose of this study was to determine the above-ground carbon value in the mangrove forest Karang Sewu, Bali, using Sentinel-1A imagery. Estimation of above-ground carbon in SAR images using the sigma nought Vertikal Horizontal polarization method based on carbon estimation models from field data and image data. The best carbon estimator model is a polynomial model with the equation y = 0.1055x2 + 4.1507x + 43,691, R2 = 0.3347. The Root Mean Square Error (RMSE) error rate is 0,7. Based on the RMSE value, it can be concluded that the difference between the field carbon and the image carbon results is relatively small The estimation result of the total above-ground carbon value using Sentinel-1A imagery is 59.85 tons/ha.